INDAPSON: An Incentive Data Plan Sharing System Based on Self-Organizing Network - Yu, Tuo; Zhou, Zilong; Zhang, Da; Wang, Xinbing; Liu, Yunxin; Lu, Songwu (INFOCOM 2014, 2014)
The contradiction between dynamic user traffic and fixed data plans has drawn increasing attention in the field of mobile applications. In this paper we build a data plan sharing system named INDAPSON to consider a scenario where some smartphone users have surplus data traffic and are willing to help others download data. Virtual credits can be gained as reward, which can be used to ask for future help in downloading. To realize this model, we make the following contributions: 1) A dynamic self-organization strategy to adapt to mobile terminals; 2) An incentive mechanism named RAP to encourage participation; 3) Power-saving strategies to reduce power consumption. The main advantage of our system is that users gain improvement in download rate while being able to convert their surplus data traffic to virtual credits. The results of experiment and simulation show that users in our system can manage their surplus data plan more efficiently while a highspeed download rate can be achieved.